AN ANALYSIS OF LESSON PLAN BASED ON THE 2013 CURRICULUM IN TEACHING ENGLISH - Asyiah, Ilma Nurul (2015)
This study investigated whether the lesson plans made by two teachers in one Senior High School in Tasikmalaya, West Java were based on the 2013 Curriculum or not. This study also investigated the difficulties faced by the teachers in developing lesson plans in teaching English. This study used a qualitative descriptive method. The data were obtained through documentation and interview. To gain the results of document analysis, the lesson plans from two teachers were analyzed in terms of core competence and basic competence, indicators, objectives of the study, teaching materials, teaching method, teaching activity and assessment. Finally, the interview data were analyzed by transcribing, categorizing, and interpreting the data by relating them to the theory. The results revealed that the lesson plans made by the teachers were relevant to the 2013 Curriculum as stated by the Ministry of Education and Culture of Republic of Indonesia. On the other hand, there were some components of the lesson plans which were not relevant to the 2013 Curriculum. Moreover, the interview data showed that the difficulties faced by the teachers in developing lesson plans included to differentiate the students' needs and interest in learning materials, to adjust between learning materials and the right method, and to arrange learning activities. Based on the data, this recommended that a longitudinal study be conducted to deal with the whole classroom activity to find out its relevancy with what has been stipulated in the national curriculum. Keywords: Lesson Plan, the 2013 Curriculum, Core Competence, Basic Competence.